Is tDCS an Adjunct Ergogenic Resource for Improving Muscular Strength and Endurance Performance? A Systematic Review - Machado, Sergio; Jansen, Petra; Almeida, Victor; Veldema, Jitka (Frontiers in Psychology, 2019)
Background: The non-invasive brain stimulation can modulate neural processing and therefore has the potential to improve the motor performance in exercises and sports. Methods: We review the pertinent literature prior to 20/02/2018 on transcranial direct current stimulation in promoting the muscle force and the endurance in healthy adults. Results: We found 30 trials (they included 539 subjects). The analysis of the data shows positive effects of anodal transcranial direct current stimulation and no significant effect of cathodal direct current stimulation on improving both the muscle force and the endurance. Conclusion: The anodal tDCS has the potential to influence positively the performance in sports and exercise, but the current knowledge is insufficient for its routine use.